Study on Supply Chain Model with Stochastic Demand, Rework, Trade-credit, Variable Transportation Cost and Lead-time Dependent Ordering Cost Reduction - Monami Das Roy (New Approaches in Engineering Research Vol. 9, 2021)
This study investigates a vendor-buyer supply chain system where the lead time demand is normally distributed. Imperfect production and rework of defectives are considered. The reduction of lead-time and ordering cost act dependently. Trade-credit financing and variable transportation cost are also taken into consideration. The aim of this study is to maximize the joint expected total profit by providing an inter-dependent reduction strategy of lead-time and ordering cost and also determine the optimal values of number of deliveries, lead-time, order lot size, ordering cost, and lead-time crashing cost. A suitable solution algorithm and a numerical example are presented to establish the model.